FACTORS AFFECTING THE LAW ENFORCEMENT OF THE PEKANBARU CITY REGIONAL GOVERNMENT ON SHOCKED MARKET ACTIVITIES DURING THE COVID-19 PANDEMIC IN 2020 (STUDY ON THE SHOCK MARKET IN TENAYAN RAYA DISTRICT) - Nurmei Minta Ito; Adlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
In recent years, many shocked markets have emerged in a number of sub-districts in Pekanbaru City. As of 2020 the market totals 71 markets. A shock market is a market that stands on a place or land owned by residents and is not managed by the Pekanbaru City Trade and Industry Office, so it is also called an unofficial market. However, in 2020, precisely on March 20, 2020, Indonesia was hit by the Covid-19 pandemic by the Corona Virus, this caused restrictions on community activities in various fields. Coinciding with anticipating the spread of the Corona virus (Covid-19), the Beleidsregel issued by the Pekanbaru City Industry and Trade Office on March 28, 2020 was in the form of Appeal Letter No. 511.2 / DPP-1.1 / 355 concerning Anticipation of the Spread of the Corona Virus (Covid-19). The content of the letter is to be able to stop market activities because the shock market operates illegally and does not have legal legality and avoids crowds to prevent the spread of the Corona Virus or Covid-19. This study aims to determine the factors that affect the ability of the Department of Industry and Trade to force the enactment of a letter of appeal through law enforcement of the Pekanbaru City Regional Government against Shocked Market Activities During the Covid-19 Pandemic to stop the spread of the Corona virus which is seen using law enforcement theory according to Soerjono Soekanto. The location of the study was carried out at the Department of Industry and Trade and the Pekanbaru City PP Satpol Office. This research uses qualitative research methods, the data collection techniques used are observation, interviews and documentation. The result of this study is the Law Enforcement of Pekanbaru City Regional Government against Shocked Market Activities During the Covid-19 Pandemic in 2020 at the Shock Market in Tenayan Raya District, especially Beleidsregels in the form of appeal letter No.511.2 / DPP-1.1 / 355 has not run optimally which is caused by several factors, namely the less strict Beleidsregels sanctions, special regulations on the market that do not yet exist and the low legal awareness of the people themselves. Keywords: Beleidsregels, Covid-19, Law Enforcement, Shocked Market